Effects of Cu on the microstructures and tensile properties of thixoformed Al-Si alloys - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Alhawari, Khalid Salim; Mohammed, Mohamad Naser (Trans Tech Publications, Switzerland, 2015)
In this study, the effects of copper content on the microstructures and tensile properties of thixoformed Al-5Si-xCu-0.5Fe (x =1.0, 2.0 and 3.0wt. %) were investigated. For this study, three different alloys having various amounts of copper were prepared using cooling slope casting before thixoforming. The semi-solid liquid range for the alloys were estimated using the diffrential scanning calorimetry (DSC) analysis. The samples were thixoformed at 40% liquid fraction. Some of these samples were treated with a T6 aging process. The thixoformed and thixoformed T6 samples were then characterized by optical microscopy, scanning electron microscope (SEM) and energy dispersive X-ray (EDX) as well as tensile tests. The different phases formed in the thixoformed and thixoformed T6 samples were throughly investigated.The results indicate that as copper content increases, the tensile strength also increases, which might due to precipitation hardening. The thixoformed T6 alloys attained an ultimate tensile strength (UTS) as high as 303 MPa when Cu content is 3.0wt.%.